Οι Γερμανοί ξανάρχονται... Τι έκανες στον πόλεμο Θανάση; Η ιστορική μαρτυρία και η πολιτική λειτουργία δύο σατιρικών κωμωδιών - ΜΟΥΡΑΤΙΔΗΣ ΠΑΡΑΣΚΕΥΑΣ (Μνήμων, 2011)
This article refers to the potential use, as historical source of two satirical comedies, the movies “Οι Γερμανοί ξανάρχονται” (1947) and “Τι έκανες στον πόλεμο Θανάση;” (1971). The theoretical basis which underlines the article is that Greek post-war cinema offers to the historian a priceless source material for the study of recent Greek history. The choice of the specific movies is justified by the common fundamental elements which they, not by chance, share. Both of them were showed in historically crucial periods. The first, at 1947, during –at the beginning indeed– of the Greek Civil War. The second, at 1971, the last years of the military Dictatorship. Both of them, as they seemingly refer to the Germans Occupation of Greece, exercise criticism on their contemporary totalitarian regimes. The fact that they were produced under these vicious circumstances does not reduce their political significance. Both of them, were extraordinary successful. This choice from the audiences is precisely what gives us an insight look of their attitudes and feelings. For the same reason they strongly influenced “public opinion” and provoked harsh political dialogue through the press as well intense political reactions. In our opinion, these two movies reflect the “common sense” for the given historical moments, as they illuminate the internal political and ideological motivations of the majority of the middle-class. Or, generally thinking, the majority of people who, during the Civil War or the Junta, placed themselves against the Regime, although they were not willing to directly resist to the official decisions. In sum, we believe that film research offers a considerable source material, one that does not replace traditional history sources, but adds to them. Moreover, this new approach may be proved more attractive or effective when we try to familiarize younger audiences with recent Greece’s political History.